Envy as Pain: Rethinking the Nature of Envy and its Implications for Employees and Organizations - TAI, Kenneth (Institutional Knowledge at Singapore Management University, 2012)
Although envy has been characterized by resentment, hostility, and ill will, researchers have begun to investigate envy's benign manifestations. We contend that the substance of envy has been confounded with its consequences. We conceptualize envy as pain at another's good fortune. This reconceptualization allows envy to result in both positive and negative consequences. We then examine how envy affects interpersonal behaviors and job performance, contingent on core self-evaluation, referent cognitions, and perceived organizational support.